Antioxidant, Anti-urease Activities and Genotoxic Effects of Terfezia Claveryi Methanol Extracts on Human Lymphocytes - ŞENKARDEŞ, İSMAİL; TAŞKIN, TURGUT; YEŞİL, TUĞÇE (MARMARA UNIV, INST HEALTH SCIENCES, 2018)
Objective: Terfezia claveryi is a dark brown color truffle and has been used extensively in human diet in Turkey. Therefore; it is an important issue to determine their biological activities and toxicity. This study aims to investigate the antioxidant and anti-urease effects of T. claveryi methanol extracts and to evaluate the genotoxicity of each extract. Methods: The antioxidant activities of methanol extracts were examined by 2,2-diphenyl-1-picryl-hydrazyl (DPPH), 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonate (ABTS) and ferric reducing/antioxidant power (FRAP) methods. The amount of total phenolic compounds contained in the extracts was determined using the Folin-Ciocalteu reagent (FCR) method. Anti-urease activities of methanol extracts were evaluated by indophenol method. In addition, potential DNA damaging effects of T. claveryi extracts on human lymphocytes were determined by the alkaline comet assay. Results: UM extract exhibited higher DPPH radical scavenging activity than MM extract [the concentration of the substance which provides the inhibition of 50% of the radical (IC50): 0.77 +/- 0.01 mg/mL, 1.17 +/- 0.02 mg/mL, respectively, p<0.0001] however, lower activity than standard (p<0.0001). Both extracts in different concentrations of T. claveryi caused DNA damage (p<0.0001) compared with solvent control DMSO. Also, total comet scores was higher in cells which had been incubated with MM extract (p<0.05). UM extract exhibited higher ferric reducing and anti-urease activity than MM extract but not found statistically different; also activities of both extract were found lower than positive controls of each methods (p<0.0001). Conclusion: T. claveryi methanol extracts induced genotoxicity on lymphocytes and showed very low antioxidant activity compared to standards. This preliminary study should be confirmed with further studies and in different cell lines.
Keywords: T. claveryi; genotoxic; antioxidant; anti-urease; maceration; ultrasonic bath